Renal and pulmonary thrombotic microangiopathy triggered by proteasome-inhibitor therapy in patient with smoldering myeloma: A renal biopsy and autopsy case report. Issue 39 (September 2019) - Cassol, Clarissa A.; Williams, Michael P.A.; Caza, Tiffany N.; Rodriguez, Sophia
Abstract: Rationale: Thrombotic microangiopathy (TMA) is a group of clinical syndromes characterized by excessive platelet activation and endothelial injury that leads to acute or chronic microvascular obliteration by intimal mucoid and fibrous thickening, with or without associated thrombi. It frequently involves the kidney but may involve any organ or system at variable frequencies depending on the underlying etiology. Among its numerous causes, drug toxicities and complement regulation abnormalities stand out as some of the most common. A more recently described association is with monoclonal gammopathy. Lung involvement by TMA is infrequent, but has been described in Cobalamin C deficiency and post stem-cell transplantation TMA. Patient concerns: This is the case of a patient with smoldering myeloma who received proteasome-inhibitor therapy due to retinopathy and developed acute renal failure within one week of therapy initiation. Diagnoses: A renal biopsy showed thrombotic microangiopathy. At the time, mild pulmonary hypertension was also noted and presumed to be idiopathic. Interventions: Given the known association of proteasome-inhibitor therapy with thrombotic microangiopathy, Bortezomib was discontinued and dialysis was initiated. Outcomes: Drug withdrawal failed to prevent disease progression and development of end-stage renal disease, as well as severe pulmonary hypertension that eventually lead to the patient's death. Lessons: To our knowledge, this is the first reported case of pulmonary involvement by TMA associated with monoclonal gammopathy which appears to have been triggered by proteasome-inhibitor therapy. Clinicians should be aware of this possibility to allow for more prompt recognition of pulmonary hypertension as a potential manifestation of monoclonal gammopathy-associated TMA, especially in patients also receiving proteasome-inhibitors, so that treatment aiming to slow disease progression can be instituted.